(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
In the article, the language of performance was explored for its disruptive power, serving as a platform for experimenting with creative solutions to conventions produced by heterosexuality. Diana Torres’s pornoterrorist performance materialized artistic strategies to destroy hegemonic narratives about gender and sexuality, thus presenting itself as an important reference in the investigation of producing critical images of the heteronormative imagination. The creation of the performance Cualquiera! Qualquer cosa sobre todo en mi, presented in the article, was based on pornoterrorist foundations, influencing artistic resistance strategies.